2020
DOI: 10.3390/ani10122267
|View full text |Cite
|
Sign up to set email alerts
|

Insights into German Consumers’ Perceptions of Virtual Fencing in Grassland-Based Beef and Dairy Systems: Recommendations for Communication

Abstract: The share of cattle grazing on grassland is decreasing in many European countries. While the production costs of intensive stall-based beef and dairy systems are usually lower per kg product, grazing-based systems provide more ecosystem services that are valued by consumers. Innovative grazing systems that apply virtual fencing technology can improve animal welfare, optimize grassland use as pasture, and contribute to biodiversity conservation. Although consumer demand for pasture-raised products could promote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…However, this is illegal in a number of European countries including Denmark, under current regulations. Moreover, animal welfare has been shown to be a concern for the public when it comes to implementing virtual fencing technology [ 11 ]. Thus, to determine whether virtual fencing is suitable for use in nature conservation, it has to be ensured, that welfare is not compromised.…”
Section: Introductionmentioning
confidence: 99%
“…However, this is illegal in a number of European countries including Denmark, under current regulations. Moreover, animal welfare has been shown to be a concern for the public when it comes to implementing virtual fencing technology [ 11 ]. Thus, to determine whether virtual fencing is suitable for use in nature conservation, it has to be ensured, that welfare is not compromised.…”
Section: Introductionmentioning
confidence: 99%
“…Virtual fencing systems have promise to control livestock movements, but the cost of the devices compared to traditional fencing may limit adoption by rangeland livestock producers (Banhazi et al, 2012;Umstatter et al, 2015). In addition, the public may have concerns with virtual fencing (Stampa et al, 2020). For example, Markus et al (2014) found that cattle avoided an excluded area days after the virtual fencing system was discontinued, while cattle readily entered the excluded area when electric fencing was dismantled.…”
Section: Virtual Fencingmentioning
confidence: 99%
“…In contrast, Campbell et al (2019b) found that fecal cortisone levels were similar for cattle constrained virtual fencing and traditional electric fencing. Virtual fencing may become a prominent tool in precision livestock management if educational programs are developed to address public concerns with the welfare of livestock constrained by virtual fencing (Stampa et al, 2020), and the cost of virtual fencing equipment drops to a level comparable to labor, material and maintenance costs of traditional fencing.…”
Section: Virtual Fencingmentioning
confidence: 99%
“…The general public have raised concerns about technologies such as virtual fencing. Many of the studies of virtual fencing have been directed to address these concerns (e.g., Campbell et al, 2019), though efforts to provide that information to the general public will also need to be made to aid with its use (Stampa et al, 2020).…”
Section: Limitations and Challengesmentioning
confidence: 99%